The Use of Iraqi Porcelanite Rocks for Purification of Drinking Water - Habib, Habib (Iraqi Journal of Science, 2025)
The present study was held to evaluate the performance of Iraqi porcelanite rock as a filter media in the treatment of drinking water supplies. The performance of Sand filter and dual media filter composed of porcelanite and sand were also studied.It was concluded that the porcelanite filter and/ or dual filter can be used instead of sand filter present within the local treatment plants to attain better performance due to expected performance of porcelanite without any mechanical modification of a filter.